Feasibility study of controlling and monitoring airfield lighting system at Joshua Mqabuko Nkomo international airport using scada based technology - Choeni, Humbulani (Midlands State University, 2018)
Joshua Mqabuko Nkomo International Airport was established in 1959 then known as Bulawayo Airport. It is located in the second largest city of Zimbabwe, 25 km to the north of the City of Kings- Bulawayo. JM Nkomo Airport is the second largest airport in Zimbabwe and boasts of two runways which are 2,588 meters long by 45 metres wide and 1,347 metres by 30 metres wide capable of handling wide bodied aircraft such as the Boeing 767. The airport operates 24 hours a day and is equipped with an instrument landing system in addition to airfield lighting system. These lights aid an aircraft to align with the runway and land safely as it transit from instrument approach to visual approach. At the present moment these light are controlled manually, that is, putting them on/off and controlling their brilliance from the airfield ground lighting room. During the night there are problems of controlling these lights when people have knocked off and there will only be one duty air traffic controller who will be up in the control tower. The aim of this research is to carry out a feasibility study on the possibility of using a SCADA based technology system for managing remote control airfield lights from the Air Traffic Control centre by the duty controller. The system will increase customer satisfaction, both air traffic controllers and pilots, enhance safety, and provide an accurate overview of the condition and status of airfield lighting to the user controller. More so, the SCADA system will store valuable information about alarms which might occur in the system in the field. Such data becomes handy for efficient diagnosis of a faulty system and provides hints to maintenance staff and help in restoration of the system when it breaks down.